Sistem Informasi Event Organizer Berbasis Website Pada Seven Organizer Dengan Metode Waterfall - Rengga Priyardana (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
The design of a website-based information system for event organizer services at Seven Organizer aims to improve the efficiency of admin work and provide convenience for customers in ordering services. This system is designed with an intuitive and user-friendly interface, thus facilitating interaction between users and the system. With the implementation of this information system, data management becomes more effective and efficient, which in the end can support smooth operations, especially for admins. This study aims to design and build a website-based event organizer service information system using the Waterfall software development method.